GENERAL STRENGTH OPTIMIZATION BY AEROBIC GYMNASTICS SPECIFIC MEANS IN ADULTS - Aida Petrea; Elena Rață (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In this article, we aim to find the most effective means specific to aerobic gymnastics that contribute visibly to optimize the general strength in adults. To this effect, exercise programs were chosen, corresponding to the morpho-functional peculiarities of these persons, taking into account the previous medical condition and motor experience. We chose aerobic gymnastics because it is a dynamic activity that contributes effectively to the optimization of the general strength by modeling the human body, to the increase the motor development indices and hence of the quality of life.